Having one’s complaint heard: Implicit knowledge in prison disciplinary reports - Danais-Raymond, Esther; Robert, Dominique (Criminologie)

(untitled) (Les Presses de l’Université de Montréal, 2022)
The competence of correctional officers is judged based on their capacity to maintain order within a particular sector of a prison. In rare instances, however, an officer may decide to refer a problematic situation to a disciplinary committee. Pragmatic sociology suggests that such referrals should be viewed as complaints whose validity can be decided only if the implicit knowledge they rely on is understood. Our discursive analysis of one year of disciplinary reports from a Quebec prison allows us to identify the orders of worth and interpretations used in complaints by correctional officers. This exploration of the form and content of disciplinary reports suggests that such documents play an important role as mediators between different levels of prison authority.